2010
DOI: 10.1002/ijc.25440
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal stem cells enhance growth and metastasis of colon cancer

Abstract: Recently, mesenchymal stem cells (MSCs) were reported to migrate to tumor stroma as well as injured tissue. We examined the role of human MSCs in tumor stroma using an orthotopic nude mice model of KM12SM colon cancer. In in vivo experiments, systemically injected MSCs migrated to the stroma of orthotopic colon tumors and metastatic liver tumors. Orthotopic transplantation of KM12SM cells mixed with MSCs resulted in greater tumor weight than did transplantation of KM12SM cells alone. The survival rate was sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
218
3
2

Year Published

2013
2013
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 262 publications
(231 citation statements)
references
References 40 publications
8
218
3
2
Order By: Relevance
“…It is now well established that MSCs migrate to and engraft at the site of many tumour types, including colorectal tumours [6], with conflicting reports on a pro-or anti-tumorigenic role [22]. Due to the remarkable tumour-specific homing capacity of MSCs, they may play a role as tumour targeted delivery agents [22].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is now well established that MSCs migrate to and engraft at the site of many tumour types, including colorectal tumours [6], with conflicting reports on a pro-or anti-tumorigenic role [22]. Due to the remarkable tumour-specific homing capacity of MSCs, they may play a role as tumour targeted delivery agents [22].…”
Section: Discussionmentioning
confidence: 99%
“…However, the majority of studies employed an excess of MSCs to CCCs and are therefore an uncertain reflection of the physiological environment [9]. Shinagawa et al [6] observed that, following systemic injection via the tail vein, MSCs were functionally incorporated into the colorectal cancer tumour stroma where they displayed morphology and distribution similar to those of carcinoma-associated fibroblasts indicating a potential role in promoting tumorigenesis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Extensive studies have demonstrated that MSCs can migrate to the tumor site and incorporate into its microenvironment [23,24]. It has also been reported that MSCs migrate to colorectal tumors [25,26]. The common approach to study the homing of MSCs into tumor is transplanting culture expanded MSCs into animal models bearing tumor [24].…”
Section: Discussionmentioning
confidence: 99%
“…However, Karnoub et al suggested that MSCs have a supportive effect on tumor progression showing that co-injection of MSCs with breast cancer cell-line led to a higher degree of metastasis, but this effect was not significant in local tumor growth [20]. Also, the supportive effect on tumor growth by MSCs has been reported in different cancers such as colon cancer, lymphoma, and melanomas [47][48][49]. In contrast, several reports showed that MSCs may have a suppressive role in tumor development via p38 mitogen-activated protein kinases (MAPK) or by cell fusion [50,51].…”
Section: Discussionmentioning
confidence: 99%